The acute effects of lower limb blood flow restriction on physiology and performance of competitive cyclists - Lander, P.; Paton, C. D. (Journal of Science and Cycling, 2019)
Background: Training in conjunction with limb Blood flow restriction (BFR) is an increasingly popular method of producing increased physiological stress without the strain of high exercise loads. However little is known about the physiological responses to BFR with trained cyclists or how best to prescribe appropriate BFR training intensities.